The Effect of Paired Down Passing Practice and Individual Drill Practice on Volleyball Down Passing Ability - Girsang, Dikky Fernando; Nofrizal, Dedi (Sekolah Tinggi Olahraga dan Kesehatan Bina Guna, 2024)
This research aims to analyze the effect of training methods in improving the volleyball underpassing ability of male students at SMP Negeri 1 Pamatang Silimahuta. The two training methods tested were paired down passing drills and individual drills. This research uses a quasi-experimental method with a quasi-experimental design. The research sample consisted of 20 students selected by purposive sampling from a total population of 273 students. This research involved two experimental groups: the first group underwent pair down passing drills, while the second group took part in individual practice drills. Data analysis techniques were carried out using descriptive and inferential statistics, including t tests for dependent samples and independent samples. The results showed that the paired down passing training method significantly improved under passing ability with an average pre-test score of 24.50 which increased to 37.00 in the post-test (t count = 12.330, t table = 3.44). A comparison between the two methods shows that the paired down passing training method is more effective than the individual drill training method, with the calculation results (t count = 3.196, t table = 2.03) showing a significant difference. In conclusion, pair bottom passing drills have a greater impact on improving students' volleyball bottom passing abilities compared to individual drill drills.